Unsteadiness In An Embedded Axial Compressor Stage - Naylor, Edward (Cranfield University, 2008)
Previous research on blade boundary layers in turbomachinery have been recognised to crucially influence the stability and performance of the gas turbine components. The interactions between rotating and stationary blade rows inevitably make the flow environment within a multistage axial compressor unsteady. Research conducted at midspan in Low Pressure turbines has shown that patches of transitional flow can withstand higher levels of deceleration, helping the boundary layer stay attached. An experimental investigation into unsteadiness in a embedded stage was conducted in the third-stage of the Cranfield four-stage Low Speed Research Compressor at two operating points: peak efficiency and near stall. This build of the Cranfield Rig was equipped with three-dimensional blading. A three-hole pressure probe was traversed at the exit of Rotor 3 in the rotating frame of reference and at the exit of Stator 3 in the stationary frame of reference. In addition measurements were made at the exit of both Rotor and Stator 3 using a slanted hotwire rotated about its axis. This measurement technique gave time-resolved three-dimensional velocities. Coupled to the exit traverses a series of boundary layer traverses were performed along Stator 3 suction surface covering the midchord region at midspan and close to the casing endwall. To aid in the understanding and interpretation of the experimental campaign, three-dimensional computations of Stator 3 were made at the two operating points using the commercial Computational Fluid Dynamics code ANSYS-CFX . A two-dimensional unsteady calculation of Rotor 3, Stator 3 and Rotator 4 at midspan and peak efficiency was also performed. The time-resolved measurements downstream of Rotor 3 showed that the rotor wake was characterised by high levels of random unsteadiness and increased incidence onto the stator row. The increase in incidence across the wake was two to three times that experienced with change in flow coefficient. Therefore the increased incidence and turbulence in a rotor wake will have a significant influence on the unsteady development of a downstream boundary layer. Measurements of the boundary layer at design condition at midspan show evidence of laminar and transitional flow up to 50% of the suction surface length. The boundary layer flow periodically undergoes transition due to the convection of the wake-induced strip that was generated close to the leading edge. Towards the casing the picture is altered slightly due to the stator-casing separation region. Boundary layer transition is completed farther forward and the transition length reduced. At off-design the picture is completely altered. Transition is completed upstream of 25% suction surface length and the flow shows only a modulating variation with blade passing. The stator-casing separation region grows in spanwise extent and the boundary layer flow on the stator surface is completely separated aft of 50% of suction surface length.